Towards design strong emergency and COVID-19 authentication scheme in VANET - Akeel kassim leaby; A. Yassin; Mushtaq Hasson; Abdullah Rashid (Institute of Advanced Engineering and Science, 2021)
The wide use of vehicular ad hoc networks (VANETs) in the last decade hasled many researchers to find efficient and reliable methods to obtain the desired benefits and offer services, such as healthcare and traffic management. However, VANETs suffer from security issues represented by authentication and data integrity. In thispaper, we propose a robust mutual authentication scheme based on elliptic curve cryptography (ECC), cryptography hash function, and a pseudonym. The proposed work was twofold in focus: first, on healthcare in emergency cars which use VANETs, and second, on overcoming security issues, such as resisting familiar attacks (e.g. insider attacks and reply attacks). Because of the serious situation generated by the worldwide outbreak of the Covid-19 epidemic, we also found this research valuable in supporting global efforts to combat the rapid spread of this virus, by finding the safest and fastest routes to epidemic treatment centres for medical staff, assistance teams in medical operations, fumigation control, and all work teams associated with disease control. This research attempts to contribute by proposing a special signal used to define epidemic teams. The best route, fast route can be chosen by using VANETs infrastructure. This scheme also deals with metric security features, such as key management, data integrity, and data privacy. In the communication and computation cost, we noticed that our proposed scheme achieved good results compared with the related works.